2013
DOI: 10.1111/ejn.12450
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of connexins associated with motoneurons in rodent spinal cord, sexually dimorphic motor nuclei and trigeminal motor nucleus

Abstract: Electrical synapses formed by neuronal gap junctions composed of connexin36 (Cx36) are a common feature in mammalian brain circuitry, but less is known about their deployment in spinal cord. It has been reported based on connexin mRNA and/or protein detection that developing and/or mature motoneurons express a variety of connexins, including Cx26, Cx32, Cx36 and Cx43 in trigeminal motoneurons, Cx36, Cx37, Cx40, Cx43 and Cx45 in spinal motoneurons, and Cx32 in sexually dimorphic motoneurons. We re-examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 85 publications
(171 reference statements)
2
19
0
Order By: Relevance
“…2, if these neurons were subject to full 3D reconstruction. It is of note that while spinal neurons have been considered to express other connexins in addition to Cx36 (Chang et al, 1999), the above accordance between our results and earlier ultrastructural work further supports our observations reported elsewhere that neuronal gap junctions in adult spinal cord are formed primarily by Cx36 (Bautista et al 2013a). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…2, if these neurons were subject to full 3D reconstruction. It is of note that while spinal neurons have been considered to express other connexins in addition to Cx36 (Chang et al, 1999), the above accordance between our results and earlier ultrastructural work further supports our observations reported elsewhere that neuronal gap junctions in adult spinal cord are formed primarily by Cx36 (Bautista et al 2013a). …”
Section: Discussionsupporting
confidence: 93%
“…Analysis of connexin mRNA and/or protein expression has suggested that multiple connexins are expressed in spinal and trigeminal motoneurons, including Cx26, Cx32, Cx36, Cx37, Cx40, Cx43 and Cx45 (Chang et al, 1999; Chang and Balice-Gordon, 2000; Chang et al, 2000; Personius and Balice-Gordon, 2000, 2001; Personius et al, 2001, 2007; Micevych and Abelson, 1991; Matsumoto et al, 1991,1992), raising the possibility that each of these connexins could form functional gap junctions between motoneurons. However, our recent analysis of connexin expression among trigeminal and spinal cord motoneurons in postnatal and adult rodent, using antibodies specific for each connexin, found labelling of only Cx36 in these neurons (Bautista et al, 2013a,b). Our results suggests that Cx36 is the major connexin mediating the electrical and dye-coupling observed between motoneurons at early postnatal ages.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our Cx36 antibody has been tested in Cx36-knockout mice [Bautista et al, 2014]. Only very slight background staining was present in this negative control (Bautista et al [2014], Fig. S1, supporting information).…”
Section: Fluorescent Labeling and Confocal Imaging For Cx36 Detectionmentioning
confidence: 95%
“…However, we tried to minimize the effects of unblinded sampling by selecting tissue areas solely based on the DAPI signal. Our Cx36 antibody has been tested in Cx36-knockout mice [Bautista et al, 2014]. Only very slight background staining was present in this negative control (Bautista et al [2014], Fig.…”
Section: Fluorescent Labeling and Confocal Imaging For Cx36 Detectionmentioning
confidence: 97%